Poor Sleep in Patients with Multiple Sclerosis - Bøe Lunde, Hanne Marie (Public Library of Science, 2012)
BACKGROUND: Poor sleep is a frequent symptom in patients with multiple sclerosis (MS). Sleep may be influenced by MS-related symptoms and adverse effects from immunotherapy and symptomatic medications. We aimed to study the prevalence of poor sleep and the influence of socio-demographic and clinical factors on sleep quality in MS- patients. METHODS: A total of 90 MS patients and 108 sex-and age- matched controls were included in a questionnaire survey. Sleep complaints were evaluated by Pittsburgh Sleep Quality Index (PSQI) and a global PSQI score was used to separate good sleepers (≤5) from poor sleepers (>5). Excessive daytime sleepiness, the use of immunotherapy and antidepressant drugs, symptoms of pain, depression, fatigue and MS-specific health related quality of life were registered. Results were compared between patients and controls and between good and poor sleepers among MS patients. RESULTS: MS patients reported a higher mean global PSQI score than controls (8.6 vs. 6.3, p = 0.001), and 67.1% of the MS patients compared to 43.9% of the controls (p = 0.002) were poor sleepers. Pain (p = 0.02), fatigue (p = 0.001), depression (p = 0.01) and female gender (p = 0.04) were associated with sleep disturbance. Multivariate analyses showed that female gender (p = 0.02), use of immunotherapy (p = 005) and a high psychological burden of MS (p = 0.001) were associated with poor sleep among MS patients. CONCLUSIONS: Poor sleep is common in patients with MS. Early identification and treatment of modifiable risk factors may improve sleep and quality of life in MS.